1998
DOI: 10.1080/014311698214316
|View full text |Cite
|
Sign up to set email alerts
|

Satellite derived crop calendar for canal operation schedule in Bhadra project command area, India

Abstract: Spatial information on crop calendars in the command areas of irrigation systems is useful to irrigation engineers in order to achieve chronological synchronization between water delivery pattern and crop life cycle. Such synchronization is vital for e cient use of water. The capability of satellite remote sensing technology to generate spatial crop calendar information in an irrigated command area and its usefulness in the evaluation of water delivery patterns are demonstrated in this paper. The study pertain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Thiruvengadachari et al [15] also used Landsat data to identify irrigation patterns in semiarid areas in India and Rundquist et al [16] used these to make an inventory of central pivot irrigation systems in Nebraska. Abderrahman et al [17] mapped the irrigated areas of the severely arid regions of Saudi Arabia using temporal Landsat Multispectral Scanner and Thematic Mapper data while Murthy et al [18] used IRS LISS (Indian Remote Sensing Satellite with Linear Imaging Self-Scanning) data to derive a cropping calendar for a canal operation schedule in India. It was Thenkabail et al [19] who demonstrated the use of time-series coarse-resolution satellite data such as those from the National Oceanic and Atmospheric Administration's (NOAA) Advanced Very High Resolution Radiometer (AVHRR) in mapping irrigated areas over the entire world.…”
Section: Introductionmentioning
confidence: 99%
“…Thiruvengadachari et al [15] also used Landsat data to identify irrigation patterns in semiarid areas in India and Rundquist et al [16] used these to make an inventory of central pivot irrigation systems in Nebraska. Abderrahman et al [17] mapped the irrigated areas of the severely arid regions of Saudi Arabia using temporal Landsat Multispectral Scanner and Thematic Mapper data while Murthy et al [18] used IRS LISS (Indian Remote Sensing Satellite with Linear Imaging Self-Scanning) data to derive a cropping calendar for a canal operation schedule in India. It was Thenkabail et al [19] who demonstrated the use of time-series coarse-resolution satellite data such as those from the National Oceanic and Atmospheric Administration's (NOAA) Advanced Very High Resolution Radiometer (AVHRR) in mapping irrigated areas over the entire world.…”
Section: Introductionmentioning
confidence: 99%
“…Geographic information system with a remote sensing component is an ideal tool for integrating the basic information sources such as maps, imagery and statistical data for effective resources management [29] . Remote sensing has shown great potential in agricultural mapping and monitoring due to its advantages over traditional procedures in terms of cost effectiveness and timeliness in the availability of information over larger areas [30] . In this study, Landsat TM and IRS P6 LISS III images were used with GIS for spatial dynamics of cropland and cropping pattern change analysis.…”
Section: Resultsmentioning
confidence: 99%
“…As noted by the FAO 26 , the crop types in northern Afghanistan include wheat, barley, rice, maize, pulses, potato, oil seed, clover, lucerne, vegetables, cotton, vegetables, melons, and opium poppy. Proper understanding of crop calendar information is essential for irrigation engineers to achieve synchronization between water delivery patterns and crop life cycles 27 . Such synchronization can contribute to efficient water usage for irrigation.…”
Section: Methodsmentioning
confidence: 99%